Cannabidiol (CBD) and Insomnia : Literature review - T. Gutierrez Higueras; F. Calera Cortés; E.D. Servin López; L. Montes Arjona; S. Sainz De La Cuesta Alonso; S. Vicent Forés (European Psychiatry, 2022)
Introduction Cannabidiol (CBD) is one of 113 cannabinoids identified in cannabis plants. Considered as a psycho-inactive component, recently, the Court of Justice of the European Union published a ruling in which it establishes that cannabidiol extracted from the cannabis plant should not be considered a drug under the United Nations Single Convention on Narcotic Drugs of 1961. Due to increased publicity on social media of the supposed benefits of this product, in addition to the lack of clear regulations, it is becoming a widely used treatment for sleep disorders.